1998
DOI: 10.1046/j.1365-2567.1998.00516.x
|View full text |Cite
|
Sign up to set email alerts
|

Human/BALB radiation chimera engrafted with splenocytes from patients with idiopathic thrombocytopenic purpura produce human platelet antibodies

Abstract: SUMMARYWe have previously shown that lethally irradiated normal strains of mice, radioprotected with severe combined immunodeficient (SCID) bone marrow, can be engrafted with human peripheral blood mononuclear cells (PBMC ). The human/mouse radiation chimera can mount marked humoral and cellular responses to recall antigens, as well as primary responses. In the present study, we adoptively transferred splenocytes from patients with chronic immune thrombocytopenic purpura (ITP) into lethally irradiated BALB/c m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…To further verify the pathogenic role of anti-GPIIb-IIIa antibodies, it is necessary to test whether thrombocytopenia can be induced by injecting anti-GPIIb-IIIa antibodies derived from patients with LC into animals, although anti-GPIIb-IIIa antibodies from patients with ITP have been shown to have a low level of cross-reactivity with mouse platelets. 40 The anti-GPIIb-IIIa antibody response was detected in patients with LC independent of the etiology, indicating that platelet-specific autoantibody production is asso-ciated with a pathogenic process shared by diverse etiologies of LC. Our previous studies on patients with ITP showed that the spleen is a primary site for both anti-platelet antibody production and platelet destruction.…”
Section: Discussionmentioning
confidence: 98%
“…To further verify the pathogenic role of anti-GPIIb-IIIa antibodies, it is necessary to test whether thrombocytopenia can be induced by injecting anti-GPIIb-IIIa antibodies derived from patients with LC into animals, although anti-GPIIb-IIIa antibodies from patients with ITP have been shown to have a low level of cross-reactivity with mouse platelets. 40 The anti-GPIIb-IIIa antibody response was detected in patients with LC independent of the etiology, indicating that platelet-specific autoantibody production is asso-ciated with a pathogenic process shared by diverse etiologies of LC. Our previous studies on patients with ITP showed that the spleen is a primary site for both anti-platelet antibody production and platelet destruction.…”
Section: Discussionmentioning
confidence: 98%
“…However, one report suggested that anti-human platelet Abs produced from splenocytes obtained from patients with ITP exhibited low crossreactivity with mouse platelets. 24 Another report showed that an anti-human ␣IIb antibody generated in mice exhibited significantly diminished binding to ITP platelets compared with normal platelets. 25 Those results suggested that the reactivity of PA anti-␣IIb␤3 Abs may be affected by subtle conformational differences between human and mouse ␣IIb␤3.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, an animal model is important to study the pathogenesis of FNAITP and to monitor potential therapeutic effects. While several models of other immune thrombocytopenia have been reported, [17][18][19] no previous animal model of FNAITP exists.…”
Section: Discussionmentioning
confidence: 99%